Experimental Investigation on the Properties of Lightweight Concrete Containing Waste Oil Palm Shell Aggregate. (2015) - Mo, Kim Hung; Alengaram, U. Johnson; Jumaat, Mohd Zamin
Abstract: This paper presents a study on the properties of a sustainable lightweight concrete incorporating high volume of waste materials. The concrete was produced utilizing lightweight oil palm shell (OPS), which is a waste material from the palm oil industry as well as manufactured sand, which is obtained from the processing of quarry waste, to replace conventional materials as coarse and fine aggregate in the concrete, respectively. In addition, ground granulated blast furnace slag (GGBS) was utilized at 20% cement replacement level to reduce the cement content in the OPS concrete (OPSC) as to further encourage the environmental-sustainability of the concrete. In the experimental study, selected properties such as the mechanical, permeation and structural properties of the OPSC were compared with those of conventional normal weight concrete (NWC) of equal targeted strength grade. While the performance of the mechanical properties such as splitting tensile strength and modulus of elasticity of the OPSC were inferior compared to NWC, the OPSC exhibited improved permeation properties such as the water absorption and sorptivity. The investigation of the structural properties such as the steel-concrete bond behavior as well as the flexural performance of reinforced concrete beam also demonstrated that the OPSC could behave similarly as NWC. The experimental results obtained in this study thus indicate the possibility of utilizing such concrete as a viable alternative for conventional NWC for practical applications.